Trajectories of Self-control in a Forensic Psychiatric Sample: Stability and Association with Psychopathology, Criminal History, and Recidivism. (September 2019) - Billen, Eva; Garofalo, Carlo; Vermunt, Jeroen K.; Bogaerts, Stefan
The current study examined trajectories of two indicators of self-control—impulsivity and coping skills—in 317 forensic psychiatric patients, as well as associations with psychopathology, crime, and recidivism. Violent recidivism was positively associated with coping skills at admission to the clinic and with impulsivity at discharge. Only a small correlation was found between self-control and criminal history, and there was no association with psychopathology. We found multiple trajectories of self-control using Latent Class Growth Models: more than 89% improving over time. In addition, patients with Cluster C personality disorders showed greater improvement in coping skills. Patients showing less improvement in impulsivity had greater rates of crime and recidivism. We conclude that self-control can be influenced by interventions or treatment, and that both starting values and trajectories of self-control provide valuable information. Interestingly, the associations between self-control and psychopathology, crime and recidivism were not as strong as reported in other populations.